2021
DOI: 10.15386/mpr-1928
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about the COVID-19 pandemic among undergraduate medical and dental students in Lalitpur, Nepal

Abstract: Background. Coronavirus disease-19 (COVID-19) has become a major global problem. There is an urgent need to measure the knowledge of the disease among health science students who can play an active role in pandemic control. The research was conducted to examine COVID-19 knowledge among medical and dental students in a Nepalese medical college, compare the knowledge to other studies in the literature and identify educational needs of students who may be involved in treating COVID-19 patients.  Methods. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
4
5
1
Order By: Relevance
“…The lower percentage of this question may be related to not being well presented on social media, TV or etc as it is a less common symptom. The correct response rate for the question about the specific treatment of the disease was 94% and slightly higher than Jha et al 4 (92.2%).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…The lower percentage of this question may be related to not being well presented on social media, TV or etc as it is a less common symptom. The correct response rate for the question about the specific treatment of the disease was 94% and slightly higher than Jha et al 4 (92.2%).…”
Section: Discussioncontrasting
confidence: 59%
“…In our study, the knowledge scores of both preclinical and clinical classes were high enough which is in accordance with the literature. 4,13,18,19 Clinical classes had higher general and professional knowledge scores than preclinical classes. This result was confirmed by Quadri et al 13 as they stated that the qualification level (interns, auxiliaries, specialists) had a significant effect on the knowledge on COVID-19.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Bearing this in mind, if policymakers work towards increasing confidence and convenience for the vaccine while decreasing complacency towards vaccine amongst the general population, they can subsequently variate the community’s intention to vaccinate significantly, this can be done by adopting tailored interventions for the context at hand concerning the different groups in the country, an approach supported in previous literature [ 42 ]. Masks are an easy and effective way to prevent COVID-19 which are reccomended majorly [ 43 , 44 ]. Less adherence to COVID-19 health behaviors i.e low practice of SOPs was established as a contributor to vaccine hesitancy in our study, this finding is consistent with a previous study done in Australia which determined the same for COVID-19 vaccine hesitancy amongst the Australian population [ 45 ], similar was also reported in a study done in the US which cited that those who reported negative COVID-19 vaccination intentions had reduced odds of more frequent adherence to social distancing and wearing masks [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The individuals who work in healthcare system still need to be conversant with the relevant knowledge with emerging threats in order to promote correct practices and protection. Scientific literatures suggest that few studies on knowledge about COVID-19 had been conducted in undergraduate medical and dental students in Nepal [11,12], but no studies has been found in HA students so far. Therefore, the purpose of this study was to assess the knowledge about COVID-19 among health assistant students studying in different paramedical colleges in Janakpurdham.…”
Section: Introductionmentioning
confidence: 99%